2010
DOI: 10.1007/s00405-010-1393-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ibuprofen on postoperative hemorrhage following tonsillectomy in children

Abstract: The objective of the study was to evaluate the effect of ibuprofen on hemorrhage after tonsillectomy in children. All charts of children, who underwent tonsillectomy with or without adenoidectomy, were reviewed. The age at the time of surgery ranged between 3 and 16 years (mean age = 7.55 ± 3.01 years). Children were divided into two groups based on the drugs used for postoperative pain relief. Group I received paracetamol after surgery. Group II received ibuprofen after surgery. A total of 62 patients receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
0
28
1
2
Order By: Relevance
“…[6][7][8][9][10] In a 2003 study by Marrett, the preoperative use of NSAIDs was associated with increased risk of reoperation for hemostasis versus those who received placebo or narcotic. 6 A study by Møiniche that same year found that postoperative NSAID use leads to increased likelihood of having a PTH requiring reoperation.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10] In a 2003 study by Marrett, the preoperative use of NSAIDs was associated with increased risk of reoperation for hemostasis versus those who received placebo or narcotic. 6 A study by Møiniche that same year found that postoperative NSAID use leads to increased likelihood of having a PTH requiring reoperation.…”
Section: Methodsmentioning
confidence: 99%
“…Les hémorragies qui font suite à cette intervention sont rares et varient entre 0,7 et 4 %, mais les conséquences d'un saignement oropharyngé peuvent être fatales 9 . Au Québec, 9000 amygdalectomies sont pratiquées chaque année, et un enfant sur 20 000 en décède 8 .…”
Section: Discussionunclassified
“…53 While there is a theoretical risk of ibuprofen use leading to increased postoperative bleeding, this adverse event has not been observed in several trials. [54][55][56][57] There is evidence that ketorolac and aspirin are associated with increased bleeding risk. 54,57 The benefit of fixed vs as-needed schedules for analgesics is unresolved, but results from one trial did demonstrate superior pain control with a fixed schedule.…”
Section: Pain Controlmentioning
confidence: 98%